How Do Basic Human Values Affect Self-Care of Type 2 Diabetes Patients? A Multicentre Observational Study. (June 2020) - Luciani, Michela; Rebora, Paola; Rossi, Emanuela; Tonoli, Luca; Androni, Silvia; Ballerini, Enrico; Fabrizi, Diletta; Riegel, Barbara; Ausili, Davide; Di Mauro, Stefania
In type 2 diabetes mellitus (T2DM) patients, human values have been identified as having a possible impact on self-care. Despite this, basic human values have never been described in the T2DM population and the association between basic human values and self-care has not been assessed. The aims of this study were to describe basic human values and self-care, and investigate the associations between basic human values and self-care in adults with T2DM. The study was cross-sectional multicentre with T2DM patients ( n = 390). Sociodemographic and clinical data were collected from charts, and two questionnaires were administered. The Portrait Values Questionnaire (PVQ) measured basic human values and allowed us to group patients into four groups based on the value profile: (A) Openness to Change and Self-Transcendence, (B) Conservation and Self-Transcendence, (C) Conservation and Self-Enhancement, and (D) Openness to Change and Self-Enhancement. The Self-care of Diabetes Inventory measured self-care maintenance, self-care monitoring, self-care management, and self-care confidence, according to the Middle-Range Theory of Self-Care of Chronic Illness. Multiple regression models were used to assess associations between the basic human values and self-care. Group D (Openness to Change and Self-Enhancement) performed significantly lower self-care maintenance ( p = .024) and self-care monitoring ( p = .031) when compared with Group A, and lower self-care monitoring ( p = .008) and self-care management ( p = .018) when compared with Group B. Group D showed significantly lower self-care monitoring ( p = .027) when compared with Group C. People with T2DM who value more self-enhancement and openness to change might be more prone to perform worse self-care compared with those who value conservation and self-transcendence. Clinicians should consider this when designing interventions aimed at improving self-care behaviors in patients with T2DM.